Healthcare and recreational sector collaboration strategies to support community-based physical activity participation among young people with childhood-onset physical disability: A scoping review protocol [version 2; peer review: 1 approved, 2 approved with reservations] - Nora Shields; Ailish Malone; Jennifer Ryan; Aoife Cooper; Karen Brady (HRB Open Research)
Objective The objective of this scoping review is to identify evidence of collaboration between healthcare and recreational sectors aimed at supporting community-based physical activity participation among young people with childhood-onset physical disability. Introduction Most young people with physical disabilities do insufficient physical activity, significantly impacting their future health. There have been long outstanding calls for collaboration between healthcare and recreational professionals to support physical activity participation for people with disabilities. Given the importance of physical activity and the roles of health and recreational professionals, there is a need to systematically identify evidence on collaborative strategies between sectors, describe the experiences of all individuals involved in delivering and receiving these collaborations and describe any outcomes measured as part of implementing these strategies. Inclusion criteria This review will include studies that involve healthcare professionals and recreational professionals working together to support community based physical activity. Specifically aimed young people aged 10 to 24 years with childhood-onset physical disabilities. Studies that report the experiences of individuals in delivering and receiving these collaborations will be included as well as studies that describe an evaluation of collaborative strategies. Methods This scoping review will be conducted in accordance with the Joanna Briggs Institute methodology of scoping reviews. A comprehensive search strategy will be developed in consultation with an information specialist. The following databases will be searched: MEDLINE, CINAHL, Embase, Web of Science and Scopus. The review will consider studies of any design that address collaboration between health and recreation sectors including qualitative, quantitative and mixed-methods study designs. Two reviewers will independently screen each retrieved title and abstract and assess full-text articles against the inclusion criteria to determine eligibility. Data will be extracted and synthesized quantitively and qualitatively and mapped to a relevant framework.